Long-Range Electron Tunneling in Aqueous and Organic Glasses - Oliver S. Wenger; Harry B. Gray; Jay R. Winkler (CHIMIA, 2005)
Photoinduced electron transfer (ET) reactions have been investigated in glassy media at 77 K. Distance decay parameters for electron tunneling through water, 2-methyltetrahydrofuran, and toluene have been determined through measurements of donor luminescence quenching by randomly dispersed electron acceptors. Remarkably different long-range ET efficiencies in the three solvents are in accord with the predictions of a super exchange model of distant electronic couplings. We conclude that tunneling energy effects play an important role in long-range ET reactions, and further that the coupling drops off very rapidly across van der Waals gaps betwee nmolecules in glasses.